The Use of Native Language in Yowis Ben The Series Episode 01 - Lukman Fahmi; Amiatun Nuryana (Program Studi Ilmu Komunikasi Fakultas Dakwah dan Komunikasi, UIN Sunan Ampel Surabaya, 2021)
The study aims to discover how Javanese social behaviour is represented on Yowis Ben movie espisode 01 through the use of native language. This study uses sociolinguistic as theoretical framework and a qualitative descriptive research approach. The findings have revealed that the usage of native language in Yowis Ben the Series Episode 01 represents Javanese social behaviour which can be seen from the conversation occurs among the communicators. From the conversations, know that they use several form of Javanese language ethics, known as unggah ungguh which is the source of Javanese language variations. Researchers have noted that this phenomenon occurs because of the position of the language and structure that is shown when we are using certain language. Cultural and social factors that exist in society attached until now one of them is what determine the use of language as a social behaviour.